The development and production of a novel Smartphone App to collect day-to-day feedback from doctors-in-training and their trainers. Issue 1 (12th December 2014) - Gray, Thomas G; Hood, Gill; Farrell, Tom
Abstract : Background: Feedback drives learning in medical education. More regular multisource feedback would improve appraisal for doctors-in-training in the UK. Trainers currently receive little feedback on supervision they provide to doctors-in-training. Barriers against providing feedback include shortage of time and lack of clear mechanisms to do so. Methods: A literature review was undertaken to investigate whether a Smartphone App to provide feedback on training was a new concept. Different training environments were identified and feedback proformas for each of these areas developed for trainers and trainees. A pre-existing logbook App identified during literature searching was modified with permission and pilot phases completed. Professional software engineering was subsequently undertaken. Results: The App developed is Healthcare Supervision Logbook . Trainers can use it for providing feedback about a trainee's performance in a clinical session and trainees can use it for providing feedback about their perceived value of the educational content of a clinical session, including the educational and/or clinical supervision they have received. Healthcare Supervision Logbook also contains a comprehensive logbook of practical procedures for all doctors using the App. It can also be used to collect patient and colleague feedback. Conclusions: Healthcare Supervision Logbook is a new concept. It allows trainers to provide daily feedback about a trainee's performance which can be used to facilitate appraisal and highlight areas for development. Feedback provided by the trainees can be used similarly to identify patterns and improve the quality of training provided. The feedback and logbook content is useful for purposes of appraisal and revalidation.